Impacts of intestinal ostomy: Perspectives on the experience of the ostomized - Constantino, Gabriel Nivaldo Brito; Santos, Daiane Lopes dos; Ribeiro, Wanderson Alves; Grassel, Cristal dos Santos; Klein, Lorena Costa; Guedes, Miriam Maria Ferreira; Carneiro, Ana Fagundes; Pires, Tarsila Reis Pinto; Siqueira, Milena Rangel; Pedrosa, Pietro Henrique Benevides; Oliveira, Ane Raquel de; Souza, Viviane Cortes Cruz de; et al. (Brazilian Journal of Science, 2024)
Stoma is a term that has the meaning of mouth. Intestinal stoma is a surgical procedure, which aims to change the path of effluents, exteriorizing part of the intestine on the surface of the abdomen. Thus, with this change, there are several impacts on the lives of individuals who are submitted to this surgical procedure. To identify through the research of articles the impacts that the ostomized go through during their experience from the religious sphere, to the labor. This is a literature review study of a qualitative approach of the reflective descriptive analysis type. The searches were conducted in the BVS and Google academic databases between February and May 2023. Inclusion and exclusion criteria were applied. Twenty-six articles were selected that were consistent with the descriptors presented and with the objective of this review. After the reflective reading, four points were raised about this population: The repercussion of the intestinal ostomy for mental health; Impacts of the intestinal ostomy in the return of the labor activities; The sexual life of the person with intestinal ostomy; The religiosity and spirituality as a support network for the person with intestinal ostomy. It is concluded that the ostomy, despite being a method that aims at improving the quality of life of the person who has it, either permanently or temporarily, generates several impacts on the experience of the ostomized person, affecting different areas. Therefore, this study is of great value in order to analyze these impacts, as well as to demonstrate them in a succinct way.